Fertility Regulation Behaviors and Their Costs : Contraception and Unintended Pregnancies in Africa and Eastern Europe & Central Asia - Lule, Elizabeth (World Bank, Washington, DC, 2013)
The report consists of three parts: global trends in fertility, contraceptive use and unintended pregnancies; studies of two regions (Africa and Eastern Europe/Central Asia) and two countries (Nigeria and Kazakhstan) on the costs of fertility regulation behaviors and provider attitudes towards contraceptive use. Fertility levels have declined steadily over the last three decades but the pace of decline varies among regions. Countries that have achieved a high level of contraceptive use have reached a lower fertility level. A gap continues to exist between actual and desired family size, resulting in unintended pregnancies. More than one-third of the pregnancies that occur are unintended and one in five pregnancies ends in induced abortion. Almost half of all induced abortions are unsafe, and the proportion of all abortions that are unsafe have increased during the last decade. Sixty-six percent of unintended pregnancies occur among women who are not using any method of contraception. Investing in quality family planning programs is a cost-effective way to address unmet need for contraception and reduce the risks of unsafe abortion, thereby improving maternal health. If contraception were provided to the 137 million women who lack access, maternal mortality will decline by 25-35 percent.